Avaliação do grau de gelificação de formulações de PVC rígido utilizando o método de ultrassom - Finocchio, Henrique (Universidade Federal de São Carlos, 2009)
The determination of the gelation degree is an important tool for predicting the properties of final products made of rigid PVC compounds. Thus, it is evident the need of a quick and effective test method that can be applied during the manufacturing process of products for quality control. In order to attend this need the ultrasound method has been applied in this work. Four rigid PVC compounds have been prepared and tested in a torque rheometer with different temperatures and times. The samples obtained, presenting different gelation degrees, have been then compression molded to obtain cubic specimens. To quantify their gelation degree the differential scanning calorimetry (DSC) technique has been applied. These specimens have been also submitted to an ultrasound testing to get their elastic constants, including the elastic modulus (E). The values of elastic modulus obtained by ultrasound have been correlated with the gelation degree obtained by DSC. In conclusion, specimens with higher gelation degrees, in general, showed higher modulus of elasticity. Therefore, it is believed that the ultrasound method may be a promising technique for evaluating PVC compounds degree of gelation and to determine their stiffness properties.
Assessment of gelation degree of rigid pvc formulations using the method of ultrasound
Keywords: Polimeros; Ultra-sam; Geliffcação; PVC; DSC (Calorimetria explorat6ria diferencial); ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA